Structural and morphological characterization of bacterial cellulose nano-reinforcements prepared by mechanical route. (15th November 2016) - Panaitescu, Denis Mihaela; Frone, Adriana Nicoleta; Chiulan, Ioana; Casarica, Angela; Nicolae, Cristian Andi; Ghiurea, Marius; Trusca, Roxana; Damian, Celina Maria
Abstract: Bacterial cellulose (BC) is a very promising material due to its high purity, good mechanical properties and thermal stability. Bacterial cellulose nanofibers (BCNF) in dry form could be used as reinforcements in hydrophobic polymer matrices like polylactic acid (PLA) or polyhydroxyalkanoates for biomedical applications. In this work, BCNF were obtained by simple eco-friendly mechanical treatments applied to BC pellicles, consisting in successive wet and dry mechanical disintegration steps or only wet mechanical disintegration followed by freeze drying. The defibrillation processes did not modify the allomorph composition of BC, characterized by the preponderance of Iα compared to Iβ form, but determined an increase of crystallinity, from 81% to 84–85%. Morphological investigations revealed that the pellicles were entirely disintegrated by the mechanical treatments. AFM Peak-Force Quantitative-Nanomechanical-Mapping revealed unexpected detachment of small fibers from the BC ribbons at regular intervals, which was proved so far only for cellulose nanofibers from plants. PLA composites obtained with these BCNF showed higher modulus with almost 30% compared to the matrix. Dried BCNF prepared by these eco-friendly approaches are good reinforcements for bionanocomposites for "in vivo" or "ex vivo" application, due to their high purity. Graphical abstract: Highlights: Bacterial cellulose nanofibers (BCNF) in dry form were obtained by simple eco-friendly mechanical treatments; The treatments did not modify the allomorph composition of BC (Iα/Iβ mixture), but determined an increase of crystallinity; BC pellicles were entirely disintegrated by the treatments, both individual and entangled BCNF being detected by SEM and AFM; BCNF are high purity reinforcements for nanocomposites useful for biomedical applications.